INVESTASI BODONG BERKEDOK ROBOT TRADING DENGAN SKEMA PONZI - Rizki Wijaya Kusuma; Efrida Ratnawati Gultom (UNES Law Review, 2023)
Businesses in Indonesia are currently experiencing rapid development following the digital era, namely by utilizing technology to facilitate the transaction process. The Indonesian financial services industry has taken advantage of a facility called fintech. Companies and individuals also feel the convenience of their business because it is assisted by fintech technology. However, in practice there are still many companies that use technology for illegal business, especially in the field of fraudulent investment with various schemes, one of which is a ponzi scheme. The research method used is normative legal research method, namely providing legal arguments in accordance with primary data and secondary data. The purpose of this study is to analyze the legal consequences for ponzi scheme actors and legal protection for ponzi scheme victims. The results of the study found that while there are no specific regulations governing ponzi schemes, the law used is Article 378 of the Criminal Code concerning Fraud Article 105 and or Article 106 of Law Number 7 of 2014 concerning Trade and or Article 4 and or Article 19 Law Number 8 of 1999 concerning Consumer Protection Article 3 and/or Article 4 and/or Article 5 and/or Article 6 in conjunction with Article 10 of the Law of the Republic of Indonesia Number 8 of 2010 concerning Prevention and Eradication of Money Laundering Crimes and preventive measures that can be taken is to periodically provide insights regarding investment to the public.